2011
DOI: 10.1111/j.1467-8624.2010.01561.x
|View full text |Cite
|
Sign up to set email alerts
|

CSRP’s Impact on Low‐Income Preschoolers’ Preacademic Skills: Self‐Regulation as a Mediating Mechanism

Abstract: Based on theoretically driven models, the Chicago School Readiness Project (CSRP) targeted low-income children’s school readiness through the mediating mechanism of self-regulation. The CSRP is a multicomponent, cluster-randomized efficacy trial implemented in 35 Head Start–funded classrooms (N = 602 children). The analyses confirm that the CSRP improved low-income children’s self-regulation skills (as indexed by attention/impulse control and executive function) from fall to spring of the Head Start year. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
583
4
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 677 publications
(623 citation statements)
references
References 77 publications
(124 reference statements)
23
583
4
13
Order By: Relevance
“…Research has also suggested that emotionally supportive and cognitively stimulating interactions with caregivers can potentially counterbalance the detrimental effects of social disadvantage (Bernier, Carlson, & Whipple, 2010;Chang, Olson, Sameroff, & Sexton, 2011). In line with this view, randomized control studies suggest that classroom interventions can support gains in self-regulation (Raver et al, 2011), but the links between typical, daily preschool experiences and the development of self-regulation have not been systematically examined.Running head: PROCESS QUALITY AND SELF-REGULATION 5 High-quality direct experiences in the classroom, referred to as process quality, may affect children's self-regulation at two levels: (a) Classroom-level quality processes, including the overall emotional, organizational and instructional climate; (b) individual-level quality processes, referring to perceived quality of the relationship between the teacher and the child which can provide nuanced information relative to a particular child's experience. In this study we consider these two core dimensions of process quality in terms of their prediction of self-regulation skills.…”
mentioning
confidence: 82%
“…Research has also suggested that emotionally supportive and cognitively stimulating interactions with caregivers can potentially counterbalance the detrimental effects of social disadvantage (Bernier, Carlson, & Whipple, 2010;Chang, Olson, Sameroff, & Sexton, 2011). In line with this view, randomized control studies suggest that classroom interventions can support gains in self-regulation (Raver et al, 2011), but the links between typical, daily preschool experiences and the development of self-regulation have not been systematically examined.Running head: PROCESS QUALITY AND SELF-REGULATION 5 High-quality direct experiences in the classroom, referred to as process quality, may affect children's self-regulation at two levels: (a) Classroom-level quality processes, including the overall emotional, organizational and instructional climate; (b) individual-level quality processes, referring to perceived quality of the relationship between the teacher and the child which can provide nuanced information relative to a particular child's experience. In this study we consider these two core dimensions of process quality in terms of their prediction of self-regulation skills.…”
mentioning
confidence: 82%
“…We examined one possible mechanism, behavioral regulation, given that it has been demonstrated that behavioral regulation is amenable to intervention (Raver et al, 2011;Sanford Derousie & Bierman, 2012). The results indicated that behavioral regulation mediated the relation between family sociodemographic risk and mathematics, but not between family sociodemographic risk and letter identification.…”
Section: The Mediating Role Of Behavioral Regulationmentioning
confidence: 99%
“…An important body of research has documented the critical role of high-quality childcare for children's development (Burchinal, Roberts, Riggins, et al, 2000;Mashburn et al, 2008). There is evidence suggesting that highquality early childhood programs promote children's cognitive, language, and socioemotional development (Bierman et al, 2008;Raver et al, 2011), but there is limited research on the associations between childcare quality and behavioral…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies show that teaching routines to children at the beginning of the year and enforcing them consistently across time increases academic achievement and reduces the frequency of problem behaviors (Johnson, Stoner, & Green, 1996;Ostrosky, Jung, Hemmeter, & Thomas, 2008). Raver et al (2011) conducted a study in the Chicago School Project 32 head start kindergarten with the participation of a total of 602 children. In the study, some instruction was given to teachers about the construction of some certain routines in the class such as rewards for positive behavior and redirection for negative behavior.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%